Negotiating spatial politics: Site-responsive urban art images in mainland China - Valjakka, Minna (China information, 2015)
Since the mid-1990s, growing urbanization has led to the rise of new forms, needs and sites for visual self-expression in urban public space in mainland China. Drawing on periods of intensive fieldwork in Beijing, Shanghai, Shenzhen and Hong Kong since 2006, this article suggests a new approach for examining the spatial politics of urban art images in China based on the concept of ‘site responsiveness’. Inspired by discussions on site-specific and site-oriented art and street art, this article aims to clarify the importance of both aesthetic analysis and comparative contextualization of urban art images in relation to (1) the reciprocal relationship between the urban art images and the site, and (2) international developments in the discourses on ‘graffiti’ and ‘street art’. This dual approach provides a starting point for a comprehensive sociospatial interpretation of the visual phenomenon in China while challenging the unproblematized use of the concept of graffiti in existing studies and offering two umbrella concepts - urban art images and creator of urban art images - to facilitate more nuanced research. By examining actions of visual self-expression at the grass-roots level, this article brings attention to an often neglected but crucial perspective to discussions of the city as a living organism and to the interrelations between art and urbanization.